2009
DOI: 10.1038/nsmb.1611
|View full text |Cite
|
Sign up to set email alerts
|

ATXR5 and ATXR6 are H3K27 monomethyltransferases required for chromatin structure and gene silencing

Abstract: Constitutive heterochromatin in Arabidopsis thaliana is marked by repressive chromatin modifications including DNA methylation, histone H3 dimethylation at lysine 9 (H3K9me2), and monomethylation at lysine 27 (H3K27me1). The enzymes catalyzing DNA methylation and H3K9me2 have been identified and mutations in these proteins lead to the reactivation of silenced heterochromatic elements. The enzymes responsible for heterochromatic H3K27me1, in contrast, remain unknown. Here we show that the divergent SET-domain p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
308
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(336 citation statements)
references
References 56 publications
19
308
1
Order By: Relevance
“…These findings suggest that histone methylation may play broad and important roles in regulating transcription. Consistent with this notion, several Arabidopsis histone methyltransferase (HMTase) mutants have been found to exhibit a myriad of developmental abnormalities (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Furthermore, transcriptome profiling studies have identified numerous genes that are misregulated in HMTase mutants (19,27,28).…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…These findings suggest that histone methylation may play broad and important roles in regulating transcription. Consistent with this notion, several Arabidopsis histone methyltransferase (HMTase) mutants have been found to exhibit a myriad of developmental abnormalities (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Furthermore, transcriptome profiling studies have identified numerous genes that are misregulated in HMTase mutants (19,27,28).…”
mentioning
confidence: 61%
“…Specifically, class I SDGs are involved in H3K27me2/3, class II in H3K36me2/3, class III in H3K4me2/3, and class V in H3K9me2 (13,19,33,34). Class IV seems to be an exception: the Arabidopsis proteins SDG15 and SDG34 are responsible for H3K27me1 (24), but it is not clear whether the two yeast homologs (SET3 and SET4) possess HMTase activity. The HMTases responsible for H3K4me1, H3K9me1/3, and H3K36me1 have yet to be determined but are likely to be uncharacterized members in these five classes.…”
mentioning
confidence: 99%
“…Inactive promoters also harbor higher levels of methylation of lysine 9 on histone 3 (H3K9Me2) (36,37). Therefore, we performed ChIP on the Mcm2 promoter with an antibody against H3K9Me2 in P 4 E 2 and E 2 treated samples 3 h after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was demonstrated that ATXR5 and ATXR6 proteins display H3K27 monomethyltransferase activity in vitro and in vivo and both are involved in heterochromatin formation and gene silencing (Jacob et al, 2009). They might also contribute to cell cycle regulation, perhaps at some stage during DNA replication, as they interact with the DNA polymerase processivity factor PCNA, and ATXR6 is a target of the E2F transcription factor (Raynaud et al, 2006).…”
Section: Histone Methylasesmentioning
confidence: 99%